IMPACT OF ORGANOPHOSPHATE PESTICIDES ON THE LIVER OF Etroplus maculatus, A FRESHWATER FISH OF KERALA, INDIA - SULEKHA, B. T.; MERCY, T. V. ANNA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
Water pollution induces histological changes in organisms like fishes and it leads to different changes ranging from biochemical alterations in single cell up to changes in fish population. The present sublethal toxicity study reveals the potential adverse effects of monocrotophos and phosphamidon, two widely used organophosphate pesticides in the paddy fields of Kuttanad, on a freshwater fish, Etroplus maculatus, a true denizen in the paddy fields of Kuttanad. Histopathology was used to assess the nature and extent of pesticide induced pathogenesis in E. maculatus. Liver plays a key role in metabolism and subsequent excretion of xenobiotics. The study reveals histological changes in liver included fatty-vacuolation and the displacement of nuclei to the periphery of the hepatocytes, coalescence of vacuoles, coagulated blood, necrosis, neoplasm, etc. Effects at the histological level are usually considered to be an early warning indicator of potential health impacts.